The contribution of autochthonous microflora on free fatty acids release and flavor development in low-salt fermented fish. (1st August 2018) - Xu, Yanshun; Li, Lin; Regenstein, Joe Mac; Gao, Pei; Zang, Jinhong; Xia, Wenshui; Jiang, Qixing
Highlights: Role of autochthonous microflora in lipolysis and flavor formation was determined. Endogenous enzymes played a major role in lipolysis. Autochthonous microflora dominated the generation of volatile flavor compounds. Abstract: To investigate the contribution of autochthonous microflora on free fatty acids (FFA) release and flavor development in low-salt fermented fish, three groups of processed fish, including bacteriostatic-acidification group (BAG), bacteriostatic group (BG), and spontaneous fermented fish (CG) were established. Results showed that addition of NaN3 reduced microbial load in BAG and BG below 3.5 log CFU/g after 3 weeks of incubation. Activities of lipases and lipoxygenase declined markedly with increasing time, where BG had the highest activities, followed by CG and BAG. There is a 36.3% higher in the total FFA content in CG than that in BAG, indicating both microbial and endogenous lipases contributed to the FFA liberation in fermented fish while endogenous lipases play a major role. However, compared to BAG and BG, largely higher levels of volatile compounds were observed in CG, suggesting that autochthonous microflora dominated the generation of volatile flavor compounds in fermented fish.